"Double‐barrel endocarditis". Issue 10 (27th June 2019) - Irabien, Ángela; Gil‐Jaurena, Juan‐Miguel; Pita, Ana; Pérez‐Caballero, Ramón; González‐Pinto, Ángel
Abstract: We report a case of an 18‐year‐old woman who presented with infective endocarditis (IE), in two conduits percutaneously delivered in the right ventricle outflow tract ("double‐barrel endocarditis"). The patient's clinical presentation, echocardiogram findings, infectious agent, clinical management, surgical approach, and follow‐up assessment are described. Percutaneous pulmonary valve implantation has emerged as a viable therapy for conduit dysfunction in the right ventricular outflow tract. Although the percutaneous approach has several advantages, this strategy and the valves used are not complication‐free. IE after transcatheter valve deployment has evoked the growing concern, as there is a higher incidence in these patients compared with patients with surgically repaired pulmonary valves. As a result, this type of surgical treatment is especially important.